THE IMPLEMENTATION OF ADIWIYATA SCHOOL CULTURE AT AL-QODIRI 1 JEMBER SUPERIOR ISLAMIC JUNIOR HIGH SCHOOL: AN ISLAMIC EDUCATION PERSPECTIVE - Wildan, Muhammad Nabilil; Rizal, Syaiful (Published by the Islamic Religious Education Study Program Faculty of Tarbiyah and Teacher Training Kiai Haji Achmad Siddiq University, Jember, East Java, Indonesia, 2025)
This study aims to analyze the implementation of Adiwiyata school culture at MTs Unggulan Al-Qodiri 1 Jember from the perspective of Islamic education. A qualitative case study approach was employed, involving purposively selected participants including the principal, teachers, students, and staff. Data were collected through observation, interviews, and documentation, and validated through source triangulation and member checking. Findings reveal that Adiwiyata values are internalized through three main strategies: habituation of eco-friendly behavior based on tauhid values, integration of khalifah and amanah concepts into the curriculum, and teacher role modeling in environmental care. The study proposes the “Islamic Adiwiyata Circle Model,” illustrating the link between spiritual awareness, ecological action, and student character formation. This model offers a novel contribution to the development of environmentally based Islamic education in madrasas. Penelitian ini bertujuan untuk menganalisis implementasi budaya sekolah Adiwiyata di MTs Unggulan Al-Qodiri 1 Jember dalam perspektif pendidikan Islam. Pendekatan kualitatif dengan desain studi kasus digunakan, dengan informan terdiri dari kepala madrasah, guru, siswa, dan tenaga kependidikan yang dipilih secara purposive. Data dikumpulkan melalui observasi, wawancara, dan dokumentasi, serta divalidasi dengan triangulasi sumber dan member check. Hasil penelitian menunjukkan bahwa internalisasi nilai-nilai Adiwiyata di madrasah dilakukan melalui tiga strategi utama: pembiasaan perilaku ramah lingkungan berbasis nilai tauhid, integrasi konsep khalifah dan amanah dalam kurikulum, serta keteladanan guru dalam menjaga lingkungan. Penelitian ini juga merumuskan “Model Lingkaran Adiwiyata Islami” yang menghubungkan kesadaran spiritual, tindakan ekologis, dan pembentukan karakter siswa. Model ini menjadi kontribusi baru dalam pengembangan pendidikan Islam berbasis lingkungan di madrasah.